Instituto Pasteur de portas abertas: uma experiência de integração com a sociedade - Iamamoto, Keila; de Oliveira Fahl, Willian; Isabel Macedo, Carla; Galera Castilho Kawai, Juliana; Ferreira, Elpidio; Corrêa Scheffer, Karin; Junior, Carnieli; Aparecida da Silva, Maria; de Carvalho Ruthner Batista, Helena Beatriz (BEPA. Boletim Epidemiológico Paulista, 2017)